Analysis of the Effects of Variable Food Packaging Seals on Tensile Test Results for PET, LDPE, and Aluminum Foil Composite Materials - Ridwan; Rizki Aulia Nanda; khoirudin, Khoirudin; sukarman, Sukarman (R.E.M. (Rekayasa Energi Manufaktur) Jurnal, 2023)
This article features experimental findings on the tensile testing procedure conducted on package seals made from Polyethylene Terephthalate (PET)-Low-Density Polyethylene (LDPE)-Aluminum Foil composite materials commonly employed in food packaging applications. This study aims to ascertain the outcomes of the tensile test or tensile strength of the packaging seal utilizing the Auto Tensile Tester XLW according to the ASTM F88 standards. The tensile test involves using two types of variables: independent variables and dependent variables. The study used temperature (°C) and holding time (s) as independent factors, whereas the dependent variable is the tensile test results or tensile strength (N/mm2). This study utilized identical parameters for each variable. The specimen's measurements were 15mm x 25mm. This experiment included three temperature factors and a constant holding time of 1 second. Every parameter underwent four tests, resulting in twelve test samples. Based on the findings, the optimal temperature range for achieving the most efficient packing sealing was 135oC. The maximum sealing strength of 17.50 N/mm2 was attained within this temperature range, and the outcomes were influenced by both the temperature and the duration of the holding period. Each sample has distinct values, encompassing a rather narrow range.